2010
DOI: 10.1007/s00424-010-0874-5
|View full text |Cite
|
Sign up to set email alerts
|

Cysteines in the loop between IS5 and the pore helix of CaV3.1 are essential for channel gating

Abstract: The role of six cysteines of Ca(V)3.1 in channel gating was investigated. C241, C271, C282, C298, C313, and C323, located in the extracellular loop between segment IS5 and the pore helix, were each mutated to alanine; the resultant channels were expressed and studied by patch clamping in HEK293 cells. C298A and C313A conducted calcium currents, while the other mutants were not functional. C298A and C313A as well as double mutation C298/313A significantly reduced the amplitude of the calcium currents, shifted t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
20
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 35 publications
(53 reference statements)
0
20
0
1
Order By: Relevance
“…However, it is important to note that redox modulation of these sites (which are conserved among T‐type channel subtypes; ref. 44) also results in large changes in voltage dependence and kinetics (44), yet inhibition by CO was not accompanied by such changes (Fig. 1).…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…However, it is important to note that redox modulation of these sites (which are conserved among T‐type channel subtypes; ref. 44) also results in large changes in voltage dependence and kinetics (44), yet inhibition by CO was not accompanied by such changes (Fig. 1).…”
Section: Discussionmentioning
confidence: 92%
“…T‐type channels are known to have extracellular redox‐sensitive sites in addition to the H191 residue of Cav3.2; Karmazinova et al (44), for example, have reported 16 extracellular cysteine residues in Cav3.1, providing much potential for redox modulation. To investigate this further, we examined the effects of cysteine.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…An alignment of the α 1G and α 1H proteins revealed that α 1H contains a similar peptide sequence in the S5–S6 loop in repeat I with sequence identity for NWNQY, as well as nearby amino acids, with the conserved Cys residue being implicated previously in channel gating activation, inactivation, and deactivation [63].…”
Section: Resultsmentioning
confidence: 98%
“…light). 32 Since ChR2 is a light-gated cation channel, the opening of this channel upon light illumination would facilitate the influx of cations and lead to an inward current flow to drive neuronal depolarization. 2, 17 The membrane-localized expression of ChR2 was first confirmed by the presence of tdTomato fluorescence using confocal microscopy (Fig.…”
mentioning
confidence: 99%